Changes in Myocardial Metabolism Preceding Sudden Cardiac Death - Snyder, J.; Zhai, R.; Lackey, A. I.; Sato, P. Y. (Frontiers in Physiology, 2020)
Heart disease is widely recognized as a major cause of death worldwide and is the leading cause of mortality in the United States. Centuries of research have focused on defining mechanistic alterations that drive cardiac pathogenesis, yet sudden cardiac death (SCD) remains a common unpredictable event that claims lives in every age group. The heart supplies blood to all tissues while maintaining a constant electrical and hormonal feedback communication with other parts of the body. As such, recent research has focused on understanding how myocardial electrical and structural properties are altered by cardiac metabolism and the various signaling pathways associated with it. The importance of cardiac metabolism in maintaining myocardial function, or lack thereof, is exemplified by shifts in cardiac substrate preference during normal development and various pathological conditions. For instance, a shift from fatty acid (FA) oxidation to oxygen-sparing glycolytic energy production has been reported in many types of cardiac pathologies. Compounded by an uncoupling of glycolysis and glucose oxidation this leads to accumulation of undesirable levels of intermediate metabolites. The resulting accumulation of intermediary metabolites impacts cardiac mitochondrial function and dysregulates metabolic pathways through several mechanisms, which will be reviewed here. Importantly, reversal of metabolic maladaptation has been shown to elicit positive therapeutic effects, limiting cardiac remodeling and at least partially restoring contractile efficiency. Therein, the underlying metabolic adaptations in an array of pathological conditions as well as recently discovered downstream effects of various substrate utilization provide guidance for future therapeutic targeting. Here, we will review recent data on alterations in substrate utilization in the healthy and diseased heart, metabolic pathways governing cardiac pathogenesis, mitochondrial function in the diseased myocardium, and potential metabolism-based therapeutic interventions in disease.